Finite Groups Having Exactly 34 Elements of Maximal Order - Han, Zhangjia; Yang, Chao (JOURNAL OF ADVANCES IN MATHEMATICS, 2015)
Let G be a finite group, M(G) denotes the number of elements of maximal order of G. In this note a finite group G with M(G) = 34 is determined.